The Effects of Feeding a Soybean-Based or a Soy-Free Diet on the Gut Microbiome of Pasture-Raised Chickens Throughout Their Lifecycle - Lourenco, Jeferson Menezes; Rothrock, Michael J.; Sanad, Yasser M.; Callaway, Todd R. (Frontiers in Sustainable Food Systems, 2019)
Soybean is one of the primary ingredients in poultry diets, but it causes problems in some consumers with allergies. Thus, production of poultry without soybean in their diets has increased in recent years. In addition, consumers are increasingly supporting alternative (e.g., organic, pasture-raised) chicken production systems for ethical reasons, yet the impacts of a variety of diets on these birds remain unclear. The present study was designed to examine the impact of feeding two different diets—a soybean-based and a soy-free diet—on the intestinal microbiome of pasture-raised chickens. 16S rRNA gene sequencing was performed on the feces, cecal contents, and whole carcass rinses from 5 pasture-raised flocks (3 soybean-based, 2 soy-free) grown over 2 years on the same farm, and their microbiomes were compared. Regardless of diet, the phylum Firmicutes corresponded to 63% or more of the total bacterial abundance in the fecal and cecal samples; however, in the whole carcass rinses, the relative abundance of Firmicutes dropped to ~30%. Alpha diversity metrics revealed significant differences without any clear patterns when comparing the 2 diets, but principal coordinate analysis of β-diversity showed significant differences (P ≤ 0.04) between them. Notably, broilers receiving the soy-free diet had lower abundance of Campylobacter during their entire lifecycle. This effect was particularly important in the fecal material collected when birds were 12-weeks-old (i.e., day of processing; P = 0.003) and in the whole carcass rinses obtained from the final product (P = 0.04). Abundance of Acinetobacter was also lower (P = 0.05) in the whole carcass rinses from birds consuming the soy-free diet. These data suggest that the presence of soybeans in chicken diets can be an important factor shaping overall microbiomes throughout the farm-to-fork continuum, specifically resulting in a greater presence of the foodborne pathogens Campylobacter and Acinetobacter. Therefore, the use of a soy-free diet can potentially represent a viable strategy to reduce contamination of carcasses in pasture-raised chicken production systems.